Controversies in Breastfeeding - Davanzo, Riccardo (Frontiers in Pediatrics, 2018)
When addressing the compatibility of breastfeeding with certain maternal conditions, we need to differentiate between “contraindication” and “obstacle”. Failure to distinguish between the two confuses new mothers and their families, and engenders misconceptions about breastfeeding advice by health professionals. Health conditions that may simply impede the initiation and duration of breastfeeding are often wrongly referred to as true contraindications to breastfeed, under the assumption that they might harm the health of the mother and/or that of the nursing infant. Here, we discuss several topics, including breast surgery, prolactinoma, concurrent new pregnancy, hormonal contraception, and use of medications and contrast agents, that continue to raise controversy. While most conditions appear to be compatible with breastfeeding, the major determinants of a woman’s final choice of whether to nurse her infant or not are the attitude of health professionals and the state of mind of being an informed mother.